SWOT ANALYSIS PERFORMA ENAM PROGRAM STUDI DI LINGKUNGAN FAKULTAS USHULUDDIN DAN ADAB (FUA) IAIN SYEKH NURJATI CIREBON TAHUN 2023 - Nuris, Anwar; Hasbunallah, Afifi (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2025)
Internally, SWOT analysis of the six environmental study programs of the Faculty of Ushuluddin and Adab has the support of young lecturers who have scientific qualifications in accordance with the peculiarities of the study program. This makes it easier to implement technology-based learning interactively with students. The students who study in the study program at the Faculty of Ushuluddin and Adab are dominated by the Ciayumajakuning area, with the origin of madrasah schools and Islamic boarding schools. Graduates of study programs at the Faculty of Ushuluddin and Adab work and have careers in various segments of the world of work with an average waiting period of less than six months. This kind of condition needs to be improved in five aspects of quality improvement, namely the Organization and Management Sector, Education and Student Affairs, Research and Community Service, Institutional Cooperation and Support Sector. These five aspects of quality improvement are carried out in the form of improvement and development strategies such as carrying out Internal Quality Audits in an accountable and database-based manner, sending lecturer delegations to scientific associations (National and International), publishing lecturer-student collaboration journals, intensifying models and cooperation from the Memorandum of Understanding (MoU) to the orientation of the Memorandum of Action (MoA), organizing the Fostered Village program.